Raising Awareness on Children's Immunity and Cognitive Abilities: Nationwide Survey to Indonesian Parents - Oktarina, Molly Dumakuri; Ibrahim, Ratih; Kinesya, Edwin; Kartjito, Melissa Stephanie; Wasito, Erika (Journal of Indonesian Specialized Nutrition, 2024)
Early life nutrition influences the development of children's immunity and cognitive abilities. According to PISA 2018, only 29% of Indonesian students have a growth students that have growth mindset. The parent’s inability to understand and improve the multifactorial aspect of cognitive development pose risk to children's cognitive growth. To raise awareness among parents to strengthen their children’s cognitive and immunity through health education. Online survey with pretest and posttest, 4 questions each, distributed to Indonesian parents that attend online seminar about impact of children's immunity toward cognitive development. The data were further analyzed with t-test using SPSS. Survey of 334 participants shows that even before the intervention, Indonesian parents understand the relation between immune system and cognitive development in children thus showing no significant difference after intervention [p-value = 0.226]. However, they did not know how to observe or measure the cognitive score such as the 8 winning skills and growth mindset, also the nutrition needed to support cognitive abilities and immunity. The intervention prove a significant increase of parent's knowledge [Pre = 1.99 ± 0.83; Post = 3.08 ± 1.11; p-value = 0.000. Indonesian parents are aware that immunity affects cognitive growth of their children. However, there is still a lack of awareness or prior knowledge on cognitive measurement tools and components, and nutrition which is beneficial for immunity and cognitive growth.